Modulation and modeling of monoclonal antibody N‐linked glycosylation in mammalian cell perfusion reactors. Issue 9 (23rd May 2017) - Karst, Daniel J.; Scibona, Ernesto; Serra, Elisa; Bielser, Jean‐Marc; Souquet, Jonathan; Stettler, Matthieu; Broly, Hervé; Soos, Miroslav; Morbidelli, Massimo; Villiger, Thomas K.
ABSTRACT: Mammalian cell perfusion cultures are gaining renewed interest as an alternative to traditional fed‐batch processes for the production of therapeutic proteins, such as monoclonal antibodies (mAb). The steady state operation at high viable cell density allows the continuous delivery of antibody product with increased space‐time yield and reduced in‐process variability of critical product quality attributes (CQA). In particular, the production of a confined mAb N‐linked glycosylation pattern has the potential to increase therapeutic efficacy and bioactivity. In this study, we show that accurate control of flow rates, media composition and cell density of a Chinese hamster ovary (CHO) cell perfusion bioreactor allowed the production of a constant glycosylation profile for over 20 days. Steady state was reached after an initial transition phase of 6 days required for the stabilization of extra‐ and intracellular processes. The possibility to modulate the glycosylation profile was further investigated in a Design of Experiment (DoE), at different viable cell density and media supplement concentrations. This strategy was implemented in a sequential screening approach, where various steady states were achieved sequentially during one culture. It was found that, whereas high ammonia levels reached at high viable cell densities (VCD) values inhibited the processing to complex glycan structures, the supplementation of either galactose, or manganese as well as their synergy significantly increased the proportion of complex forms. The obtained experimental data set was used to compare the reliability of a statistical response surface model (RSM) to a mechanistic model of N‐linked glycosylation. The latter outperformed the response surface predictions with respect to its capability and reliability in predicting the system behavior (i.e., glycosylation pattern) outside the experimental space covered by the DoE design used for the model parameter estimation. Therefore, we can conclude that the modulation of glycosylation in a sequential steady state approach in combination with mechanistic model represents an efficient and rational strategy to develop continuous processes with desired N‐linked glycosylation patterns. Biotechnol. Bioeng. 2017;114: 1978–1990. © 2017 Wiley Periodicals, Inc. Abstract : Steady‐state operation of CHO cell perfusion cultures allow the continuous harvest of monoclonal antibody product with constant N‐linked glycosylation profile. Modulation of the glycan distribution is shown for several levers, including media supplementation (i.e., manganese and galactose) and bioreactor operating conditions (i.e., viable cell density) in a series of steady states according to a Design of Experiment (DoE). The resulting glycan profiles were described by a mechanistic glycosylation model, revealing superior predictive capabilities as compared to a statistic response surface. The sequential steady‐state approach in combination with mathematical models allows a rational modulation toward a desired glycan distribution constantly harvested in perfusion.